2017
DOI: 10.1155/2017/2898342
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterisation of Nobiletin-Loaded Nanostructured Lipid Carriers

Abstract: The objective of this manuscript was to investigate and optimise the potential of nanostructured lipid carriers (NLCs) as a carrier system for nobiletin (NOB), which was prepared by high-pressure homogenisation method. Additionally, this study was focused on the application of NOB-loaded NLC (NOB-NLC) in functional food. Response surface method with a three-level Box-Behnken design was validated through analysis of variance, and the robustness of the design was confirmed through the correspondence between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…The particle size of NLCs drops as the liquid lipid concentration increases (Fig. 1b), which is consistent with the results reported by Huang et al 38 It has been shown that the viscosity of melted GMS alone is higher than the viscosity of GMS and liquid lipid matrix. Therefore, this matrix of lipids can reduce viscosity and surface tension in the internal phase of NLC, which forms smaller nanoparticles.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The particle size of NLCs drops as the liquid lipid concentration increases (Fig. 1b), which is consistent with the results reported by Huang et al 38 It has been shown that the viscosity of melted GMS alone is higher than the viscosity of GMS and liquid lipid matrix. Therefore, this matrix of lipids can reduce viscosity and surface tension in the internal phase of NLC, which forms smaller nanoparticles.…”
Section: Resultssupporting
confidence: 91%
“…The "Adeq Precision" factor represents the signal-to-noise ratio of the model, which is deemed acceptable for values higher than 4. 38 The values of "Adeq Precision" for the entrapment efficiency and particle size responses are 13.602 and 13.544, respectively, which demonstrates the sufficiency of models for both responses. 3.1.2.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…TEM and DLS results are relatively identical, and the difference between TEM and DLS analysis is due to the measurement method. The DLS analysis measures the hydrodynamic diameter of particles in the solution, indicating a larger diameter for particles [22,23]. Moreover, the polydispersity index (PDI) of 0.131 reveals the uniform distribution of particles, which is aligned with AFM images (Fig.…”
Section: Characterization Of Optimized Structuresupporting
confidence: 64%
“…Drug unloaded NLC was taken as a negative control and Oleuropein drug loaded NLC as a positive control to minimize the difference between spectra due to baseline shifts. IR spectrums were compared to investigate the interaction between drug and NLC (Wei Huang et al, 2017).…”
Section: Pre-formulation Studiesmentioning
confidence: 99%